Sarawak ethnic food consumption intention amongst generation Y at UCSI University Sarawak / Joseph Martin Pudun... [et al.] - Pudun, Joseph Martin; Mohammad Nor, Zulkeplli (2016)
Despite becoming more aware of food consumption from the perspectives of nutrition, health and safety, how Malaysians perceive ethnic food and what attracts or motivates them to consume it remains largely inconclusive. The study on consumption intention behaviour of Sarawak Ethnic Food among Generation Y is important as to give insight to the Local ethnic restaurant entrepreneur to improve their products based on the finding of this study. Little are known about consumption of Sarawak ethnic food among the Generation Y, therefore this study aims to investigate the relationship between consumption intentions amongst generation Y using Theory of Planned Behaviour toward Sarawak ethnic food. A quantitative study with self-administered questionnaire was utilized. Convenience sampling method was chosen because the aim was to sample Generation Y Students in UCSI University. A total of 434 sets of questionnaires were collected from the Generation Y and pilot test was conducted to ensure the reliability of the instrument. Pearson correlation and Multiple Regression analysis result indicate that all factors have positive and significant influence consumption intention amongst Generation Y toward Sarawak Ethnic Food. Subsequently, awareness, preference, attitude, subjective norm and perceived behavioural control are found to have significant relationship among Generation Y intention consumption toward Sarawak Ethnic food. From business points of views, the finding provide a new market of Ethnic food consumers in Kuching.